A comparison of the levels and particle size distribution of lower chlorinated dioxin/furans (mono- to tri-chlorinated homologues) with those of tetra- to octa-chlorinated homologues in atmospheric samples. (May 2016) - Zhang, Xian; Zheng, Minghui; Liu, Guorui; Zhu, Qingqing; Dong, Shujun; Zhang, Hongxing; Wang, Xiaoke; Xiao, Ke; Gao, Lirong; Liu, Wenbin
Abstract: There is very little information on the levels and particle size distributions of lower chlorinated dibenzo- p -dioxins and dibenzofurans (mono- to tri-CDD/Fs, ΣCl1–3 DD/Fs) in the atmosphere, while a number of studies have examined tetra- to octa-chlorinated homologues (ΣCl4–8 DD/Fs). In this study, we measured the concentration and particle size distribution of ΣCl1–3 DD/Fs in ambient air in suburban Beijing and compared them with that of ΣCl4–8 DD/Fs for the first time. The mean concentration of ΣCl1–3 DD/Fs was 54.63 pg m −3, which is about 5.4 times that of ΣCl4–8 DD/Fs. The ΣCl1–3 DD/Fs accounted for 85% of ΣCl1–8 DD/Fs, and MoCDFs made up the largest proportion (43%) of PCDD/F homologues. The ΣCl1–3 DD/Fs mainly occurred in the gas phase, while the ΣCl4–8 DD/Fs mainly occurred in the particulate phase. The majority of ΣCl1–3 DD/Fs (70%) occurred in d ae > 1.0 μm particles, which is the reverse of the trend observed for ΣCl4–8 DD/Fs, of which 78% occurred in d ae < 1.0 μm particles. The observed high concentrations of ΣCl1–3 DD/Fs and different distribution patterns demonstrate that it is necessary to consider the lower chlorinated homologues to improve our understanding of the environmental behavior and health risk assessments of PCDD/Fs in the atmosphere. Highlights: ΣCl1–3 DD/Fs accounted for 85% of ΣCl1–8 DD/Fs in air samples. The mean concentration of ΣCl1–3 DD/Fs was 5.4 times that of ΣCl4–8 DD/Fs in the air. ΣCl1–3 DD/Fs occurred mainly in the gas phase, and ΣCl4–8 DD/Fs mainly in particles. ΣCl1–3 DFs were the dominant form of ΣCl1–3 DD/Fs in all particle size classes.